Rat cytomegalovirus efficiently replicates in dendritic cells and induces changes in their transcriptional profile - Madela-Mönchinger, Julia Cecilia; Wolf, Silver Anthony; Wyler, Emanuel; Bauer, Agnieszka; Mischke, Marius; Möller, Lars; Juranić Lisnić, Vanda; Landthaler, Markus; Malyshkina, Anna; Voigt, Sebastian (Frontiers in Immunology, 2023)
Dendritic cells (DC) play a crucial role in generating and maintaining antiviral immunity. While DC are implicated in the antiviral defense by inducing T cell responses, they can also become infected by Cytomegalovirus (CMV). CMV is not only highly species-specific but also specialized in evading immune protection, and this specialization is in part due to characteristic genes encoded by a given virus. Here, we investigated whether rat CMV can infect XCR1+ DC and if infection of DC alters expression of cell surface markers and migration behavior. We demonstrate that wild-type RCMV and a mutant virus lacking the γ-chemokine ligand xcl1 (Δvxcl1 RCMV) infect splenic rat DC ex vivo and identify viral assembly compartments. Replication-competent RCMV reduced XCR1 and MHCII surface expression. Further, gene expression of infected DC was analyzed by bulk RNA-sequencing (RNA-Seq). RCMV infection reverted a state of DC activation that was induced by DC cultivation. On the functional level, we observed impaired chemotactic activity of infected XCR1+ DC compared to mock-treated cells. We therefore speculate that as a result of RCMV infection, DC exhibit diminished XCR1 expression and are thereby blocked from the lymphocyte crosstalk.